The Political Language of Takvîm-i vekayi:the Discourse and Temporality of Ottoman ‘Reform’ (1831-1834) - Özgür Türesay (European Journal of Turkish Studies)
Based on the first years of Takvîm-i vekayi and Le Moniteur Ottoman, this study aims to shed light on the Ottoman political language and the rhetoric of the political authority in the early 1830s, focusing on one of the semantic fields that shapes it: the vocabulary of the reform. The official gazette is a corpus containing a large number of texts that express a collective political thought in the making that, beginning in 1826 when the Janissary Corps was abolished, gradually bore a new configuration of power and, inevitably, a new discourse that framed it. This discourse on reform is characterized by a future-oriented temporality in which the present is increasingly detached from the past. It is also deeply innovative by the fact that it is a discourse intended to be publicized as widely as possible and is therefore intended to be pedagogical.